CLOUD NETWORK / COMPUTING IMPACT ON INTER-ORGANIZATIONAL TRUST WHICH EFFECTS PERFORMANCE OF SUPPLY CHAIN MANAGEMENT: A STUDY OF PAKISTAN’S FIRMS - HAMZA ALI MANSOOR; DR. MUHAMMAD ASIM; SALMAN MANZOOR (CenRaPS Journal of Social Sciences, 2020)
This paper analyzes Cloud Computing Impact on Inter-organizational Trust which affects the performance of Supply Chain Management of different Retail, Manufacturing, Financial, IT and Services firms in Karachi, city of Pakistan. A theoretical framework has been constructed that illuminates the role of Inter-organizational Trust in Cloud Computing (CC) and how this can reproduce the superior performance of Supply Chain (SCP) by using arguments of the Social Capital Theory (SCT). A questionnaire was run on 200 individuals having a different position like Senior Manager, Middle Manager and Officer of different Retail, Manufacturing, Financial, IT and Services firms in Karachi, state of Pakistan, and statistically analyze the hypothesis by step by step regression test. The result suggests that Cloud Computing (CC) would be controlled to support Inter-organizational Trust (IOT) to have a strong and significant influence on the association of Supply Chain. To improve complete Inter-organizational Trust (IOT) terms and conditions in organizations managers have to implement Cloud Computing base which creates radical improvement in Supply Chain Performance and the results, therefore, reinforce the across the board to explanation augured by the useful theoretical framework as Social Capital Theory (SCT).